2016
DOI: 10.20944/preprints201611.0072.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis and Structure-Activity Relationships of a Series of Aporphine Derivatives with Antiarrhythmic Activities and Acute Toxicity

Abstract: Some aporphine alkaloids, such as crebanine, were found to present arrhythmic activity and also higher toxicity. A series of derivatives were synthesized by using three kinds of aporphine alkaloids (crebanine, isocorydine, and stephanine) as lead compounds. Chemical methods, including ring-opening reaction, bromination, methylation, acetylation, quaternization, and dehydrogenation, were adopted. Nineteen target derivatives were evaluated for their antiarrhythmic potential in the mouse model of ventricular fibr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Preliminary structure-activity relationship (SAR) investigation indicated that the presence of a double bond at the 6a,7-position of dehydrostephanine resulted in an increase of anti-inflammatory activity. Increased skeletal rigidity and conjugation of dehydrostephanine may facilitate the infusion of the dehydrogenated compound to the cells and thus leading to its biological effect [32]. Taken together, aporphine alkaloid dehydrostephanine exhibited anti-inflammatory effect by suppression of inflammatory mediators NO and pro-inflammatory cytokines and this may be involved at least in part in the suppression of several signaling pathway activation.…”
Section: Anti-inflammation Of Dehydrostephaninementioning
confidence: 99%
“…Preliminary structure-activity relationship (SAR) investigation indicated that the presence of a double bond at the 6a,7-position of dehydrostephanine resulted in an increase of anti-inflammatory activity. Increased skeletal rigidity and conjugation of dehydrostephanine may facilitate the infusion of the dehydrogenated compound to the cells and thus leading to its biological effect [32]. Taken together, aporphine alkaloid dehydrostephanine exhibited anti-inflammatory effect by suppression of inflammatory mediators NO and pro-inflammatory cytokines and this may be involved at least in part in the suppression of several signaling pathway activation.…”
Section: Anti-inflammation Of Dehydrostephaninementioning
confidence: 99%